Hypotonia in Kwazulu Natal - prevalence and causes - P. M. T. Dawson; T. Puckree (AOSIS, 2006)
Benign Congenital Hypotonia (BCH) is a condition whose specific diagnosis and causes are elusive. Time and intensive diagnostic screening allows for unmasking of a specific diagnosis in some cases. The remaining cases are considered to have a good prognosis with resolution by adolescence. For physiotherapy to facilitate development in the intervening period, knowledge of prevalence and causes of the disorder is para mount. Limited information on prevalence of "BCH" exists in the world and none exists for either KwaZulu Natal or South Africa. This study investigated the prevalence of, and precipitating factors for Hypotonia in KwaZulu Natal. Four hundred children aged 6-7 years, from 16 schools in 8 educational zones participated in the study. The Standardized Motor Test Battery was used to differentiate normal children from those with signs and symptoms of BCH. 101 children tested positive for Hypotonia. Questionnaires to determine potential causes of Hypotonia were administered to these children and an age-matched cohort of 400 normal children.  The main predictors of Hypotonia were assisted vaginal delivery and reduced physical activity. We conclude that Hypotonia is a significant, unrecognized disorder amongst our children. Prevention should be the goal of primary health care to reduce the prevalence.